The Birth of Compassion - Mona Sugianto (Budapest International Research and Critics University, 2020)
The concept of suffering is as old as human history. Efforts to reduce and eliminate suffering have been done in various ways. One of them is compassion, which is an effort to reduce and eliminate the suffering of others. The purpose of this study is to describe the manifestations of compassion that are present in daily life and to understand the process of how acts of compassion are born. A qualitative phenomenological approach was chosen using reflections on life experiences of 1066 participants (Men = 392, Women = 674, range of age 12-65 years) who lived in Jakarta, Indonesia. The results of the study revealed that he manifestations of compassion in daily life can be grouped into two major parts, namely tangible compassion and intangible compassion. Tangible compassion consists of financial support, material goods, helping behavior, and involvement in social activities. While intangible compassion consists of emotional support, companion support, informational support, spiritual support, forgiveness, sacrifice & serve, and others. The birth process of compassion begins with a reflection of a personal suffering experience, empathy for the suffering of others, and inspiration from the goodness of others. These three things create concern. Concern allows one to discover the driving and pulling factors of compassion, which after being tested by overcoming challenges and finding opportunities, will be mature for a decision to be compassionate, and give birth to acts of compassion.